Analisis Studi Kasus Penggunaan Minecraft: Education Edition dalam Pembelajaran Matematika Kelas V di MIN 02 Batang (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
The rapid digital transformation has introduced new challenges in education, particularly in making mathematics learning engaging and contextual at the elementary level. A crucial issue lies in the low interest and engagement of students due to conventional teaching approaches that are often perceived as boring and abstract. This study aims to analyze the use of Minecraft: Education Edition as an innovative digital learning medium to enhance the effectiveness of mathematics instruction in the fifth grade of MIN 02 Batang. A case study approach was employed, utilizing observation, interviews, and documentation during the learning process. The findings indicate that Minecraft significantly increases student engagement and facilitates the understanding of concepts such as geometry, measurement, and scale through visual and contextual exploration. Supporting factors include student enthusiasm and available digital infrastructure, while obstacles include time limitations and teacher readiness in using technology. In conclusion, Minecraft: Education Edition holds significant potential as a 21st-century learning tool that is adaptive and enjoyable, with recommendations for teacher training and more effective time planning in classroom implementation.